Learning English through YouTube videos to foster speaking skills: Public Administration students’ perceptions - Fu'ad Sholikhi (English Language Education Study Program, Faculty of Education and Teacher Training, Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, Indonesia, 2023)
Many teachers use YouTube as an internet-based application to share their areas of expertise, such as sharing writing skills, English pronunciation, English speaking, and so on. In this research, the lecturer uses YouTube as an audiovisual application to help Public Administration students learn English speaking. This research fills the gap of previous research in higher education, precisely about learning to support their careers in the near future. This research aims to understand YouTube as a medium for speaking English based on Public Administration students’ perceptions in class. Therefore, the qualitative method was ideal to answer the purpose of the research. This study involved 15 students, and the researcher served as the primary instrument because of his capacity to provide clarity about the phenomenon utilizing questionnaires and semi-structured interviews. The finding showed that YouTube was the right tool to support their speaking skill. YouTube enhances students’ understanding of Public Interest vocabulary. However, a stable internet connection was the most common problem in learning. Furthermore, there must be similar research in the Department of Elementary School Teacher Education to fill the gap in this research and enrich the understanding of English-speaking skills.